The TLR2/6 ligand PAM2CSK4 is a Th2 polarizing adjuvant in Leishmania major and Brugia malayi murine vaccine models. Issue 1 (December 2016) - Halliday, Alice; Turner, Joseph; Guimarães, Ana; Bates, Paul; Taylor, Mark
Abstract Background Toll-like receptors (TLRs) play an important role in the innate and adaptive immune responses to pathogens, and are the target of new vaccine adjuvants. TLR2 plays a role in parasite recognition and activation of immune responses during cutaneous leishmaniasis infection, suggesting that TLR2 could be targeted by adjuvants for use inLeishmania vaccines. We therefore explored using Pam2 CSK4 (Pam2) and Pam3 CSK4 (Pam3) lipopeptide adjuvants, which activate TLR2/6 and TLR2/1 heterodimers respectively, in vaccine models for parasitic infections. Methods The use of lipopeptide adjuvants was explored using two vaccine models. For cutaneous leishmaniasis, the lipopeptide adjuvants Pam2 and Pam3 were compared to that of the Th1-driving double-stranded DNA TLR9 agonist CpG for their ability to improve the efficacy of the autoclavedLeishmania major (ALM) vaccine to protect againstL. major infection. The ability of Pam2 to enhance the efficacy of a solubleBrugia malayi microfilariae extract (Bm MfE) vaccine to protect against filarial infection was also assessed in a peritoneal infection model ofB. malayi filariasis. Parasite antigen-specific cellular and humoral immune responses were assessed post-challenge. Results The use of lipopeptides in ALM-containing vaccines did not provide any protection upon infection withL. major, and Pam2 exacerbated the disease severity in vaccinated mice post-challenge. Pam2, and to a lesser extent Pam3, were able to elevate antigen-specific immune responses post-challenge in this model, but these responses displayed a skewed Th2 phenotype as characterised by elevated levels of IgG1. In theB. malayi vaccine model, the use of Pam2 as an adjuvant withBm MfE induced significant protective immunity to the same level as inclusion of an Alum adjuvant. Here, both Pam2 and Alum were found to enhance antigen-specific antibody production post-challenge, and Pam2 significantly elevated levels of antigen-specific IL-4, IL-5 and IL-13 produced by splenocytes. Conclusions These data indicate that TLR2/6-targeting ligands could be considered as adjuvants for vaccines that require robust Th2 and/or antibody-dependent immunity.